Real-world observational study to capture demographic details of newly diagnosed type 2 diabetes mellitus - Dalal, Nishant; Patel, Dixit; Chaturvedi, Alok; Shah, Ankita (International Journal of Research in Medical Sciences, 2022)
Background: To understand the demographic profile of newly diagnosed type 2 diabetes mellitus (T2DM) patients and to evaluate the glycaemic status and initial treatment choices in this subset of T2DM patients. Methods: The ROD-IT-2 study was a real-world, retrospective, cross-sectional, observational study conducted at various centres across India between April 2021 and March 2022. The study outcomes included epidemiology, comorbidities, and management strategies preferred by Indian clinicians in these patients. Results: Data from 29,550 newly diagnosed T2DM patients were analyzed. The mean age of patients was 53.3 years, and majority were males (65%). Majority of patients (63.85%) were aged 40 to 60 years. More than half (53.11%) of the patients were either overweight (36.65%) or obese (16.76%). The mean glycated hemoglobin (HbA1c) was high (8.4%). Most (88.5%) patients had cardio-renal comorbidities. Hypertension was the most common comorbidity (45.7%) followed by dyslipidemia (32.1%). Chronic kidney disease (CKD) was also present in 31.2% patients. In the present study, 9.2% patients presented with microvascular complications at the time of diagnosis. Majority of newly diagnosed patients (79.7%) were treated with combination therapy. In patients who were prescribed dual drug combination therapy, metformin + dipeptidyl peptidase-4 inhibitor (DPP4i) was the preferred combination (42.71%) followed by metformin + sulfonylurea (31.37%). Conclusions: ROD-IT-2 study showed that mean HbA1c levels in T2DM patients still remain high in our population and cardio-renal comorbidities remain prevalent in newly diagnosed patients. Indian clinicians were found to prefer the combination therapy in newly diagnosed T2DM patients.